Spliced-Leader RNA trans Splicing in a Chordate, Oikopleura dioica, with a Compact Genome - Ganot, Philippe (American Society for Microbiology, 2004)
trans splicing of a spliced-leader RNA (SL RNA) to the 5′ ends of mRNAs has been shown to have a limited and sporadic distribution among eukaryotes. Within metazoans, only nematodes are known to process polycistronic pre-mRNAs, produced from operon units of transcription, into mature monocistronic mRNAs via an SL RNA trans-splicing mechanism. Here we demonstrate that a chordate with a highly compact genome, Oikopleura dioica, now joins Caenorhabditis elegans in coupling trans splicing with processing of polycistronic transcipts. We identified a single SL RNA which associates with Sm proteins and has a trimethyl guanosine cap structure reminiscent of spliceosomal snRNPs. The same SL RNA, estimated to be trans-spliced to at least 25% of O. dioica mRNAs, is used for the processing of both isolated or first cistrons and downstream cistrons in a polycistronic precursor. Remarkably, intercistronic regions in O. dioica are far more reduced than those in either nematodes or kinetoplastids, implying minimal cis-regulatory elements for coupling of 3′-end formation and trans splicing.